The difficulties faced by bachelor teachers in classroom management at IFPI São João do Piauí, PI – Brazil, 2022 (International Seven Journal of Multidisciplinary, 2024)
Introduction: Retroperitoneal tumors (RPTs) are extremely rare tumors, predominant in both sexes, and can be malignant or benign. Due to the inaccessibility of the region and the asymptomatic or nonspecific picture, most of the time, these tumors reach a substantial size. The most frequent symptoms are abdominal pain, discomfort, or a painless palpable mass in the abdomen. In addition to the patient's clinical history, imaging tests are essential for diagnosis. Complete surgical resection is the only potential curative treatment modality for RPT. Objective: To demonstrate the importance of early diagnosis for a better prognosis and treatment of RPTs. Methods: From a medical case that occurred at the Santa Casa da Misericórdia de Presidente Prudente, and its medical records, information was collected to carry out this report. Results: Benign RPTs are approximately four times less frequent than malignant ones, which makes the patient's case even more atypical. For accurate evaluation, high-quality cross-sectional images play a key role. In the case reported here, the patient had a lesion that was difficult to access, and CT-guided biopsy was prevented, and, for this reason, the surgical choice was made. Conclusion: The success of the prognosis of RPTs is influenced by multiple factors. The grade of the tumor is of paramount importance, in addition to its intrinsic biology, along with the extent of the surgical resection performed, playing crucial roles in determining prognosis and life expectancy. Therefore, detailed imaging tests and specific laboratory tests, when possible, are crucial.